EVALUATION AN ACTIVATION ENERGY AND ITS IMPACT ON THE ELECTRICAL PROPERTIES OF CONDUCTIVE POLYANILINE - Jarad, Amer N. (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Polyaniline one of most Conductive polymer as prepared by chemical polymerization method at room temperature and studied the side effect the dopant with ionic acid such as sulfuric on the structure of the polymer. Method : The changes taking place by the following measurements: FESEM, HR-XRD, Electrical properties, and an evaluation activation energy. The FE-SEM properties of the surface study using the imaging analyzed by Field Emission Scanning Electronic Microscopic, and calculated the particle revealed, that the compound has micro granular effected with the presence of acid. Results : High resolution x-ray diffraction, crystalline nature of the polymer it has a semi-crystalline with the effect of the acid doped clear improvement happened to the installation of the crystalline nature of the polymer. Electrical characteristic study by using the 2-probe method, it found that the samples had ohmic curve. Thin films of samples that doped of polymer had a highest conductivity of 2.9x10⁻⁴ S.cm⁻¹ at 383 K, which observed for the H₂SO₄ doped sample, which shows that was more prominent of localized salted in polymeric chain. Novelty : Polyaniline one of most Conductive polymer as prepared by chemical polymerization method at room temperature and studied the side effect the dopant with ionic acid such as sulfuric on the structure of the polymer.